An Empirical Model for the Dayside Magnetospheric Plasma Mass Density Derived From EMMA Magnetometer Network Observations. Issue 2 (17th February 2020) - Del Corpo, Alfredo; Vellante, Massimo; Heilig, Balázs; Pietropaolo, Ermanno; Reda, Jan; Lichtenberger, János
Abstract: A local time dependent empirical model of the equatorial plasma mass density in the inner magnetosphere is derived from field line resonance (FLR) observations at the European quasi‐Meridional Magnetometer Array (EMMA). Models of the plasmasphere, plasmatrough, and plasmapause are derived separately and then combined. The whole model is limited to the local time (LT) sector 06:00‐18:00 and to the range of equatorial distances 2 . 3 R E < r e q < 8 R E . It is also dependent on the geomagnetic activity but only in determining the plasmapause position. It well describes the recovery phase following a plasmasphere erosion but is not intended to reproduce highly dynamical phases. The plasmasphere model is limited to the range 2 . 3 R E < r e q < 4 . 5 R E and predicts a mass density increase in the daytime sector (10–18 LT) which becomes more evident with increasing L (up to a factor of ∼ 2). A comparison with previous models of plasmaspheric electron density suggests that the diurnal variation is mainly contributed by the heavy ions. The plasmatrough model is limited to the range 3 . 8 R E < r e q < 8 R E and predicts a diurnal variation even more pronounced. Comparison with electron density models suggests that the average ion mass density can increase from ∼ 2.0 to ∼ 4–5 amu during daytime hours. An automated algorithm to search for plasmapause signatures in the radial mass density profiles derived from experimental observations is also presented. It could represent a useful space weather tool when included in a real‐time monitoring system of the plasmasphere. Key Points: An empirical model for the equatorial plasma mass density in the inner magnetosphere has been developed The modeled plasmaspheric mass density shows a diurnal variation that is mainly due to heavy ions An automatic algorithm for the identification of the plasmapause has been implemented